Penggunaan Model Investigasi Kelompok dalam Meningkatkan Kemampuan Menulis Teks Eksplanasi pada Siswa Kelas XI SMK ICB Cinta Wisata Bandung - Kusmayanti, Desti (Jurnal Artikula, 2020)
Basically everyone is capable of writing, writing skills need to be trained continuously, so that student interest can increase. Apart from needing to be trained on an ongoing basis, the selection of learning methods and models also needs to be considered, considering that students' writing skills can be categorized as still weak. This study aims to determine the feasibility of using the group investigation model to improve the ability to write explanatory texts. The research method used was a quasi-experimental design with one group pretest posttest. This research was conducted in class XI of the culinary industry at SMK ICB CintaWisata Bandung.The instruments used test and observation. The instruments are categorized valid and reliable after conducting analysis by expert judgment. The data gathered were analyzed by knowing the mean of pre test and post test, the total of the students score from pre test and post test, knowing the minimum and maximum score, and testing hypothesis by paired sample T- Test. The result of the research showed that there was an improvement from the mean of pre test 43.2 to the mean of post test 81.3.The improvement in writing explanation text of students after using the group investigation model was in accordance with the results of the gain hypothesis test, namely the probability value or Sig. (2-tailed) 0.00 <0.05.The magnitude of the increase in writing skills is indicated by the results of the hypothesis test which states that there are differences in the data from the pretest and posttest results so that there is an increase in learning by seeing the average of each activity. Thus it can be concluded that the group investigation model can improve the ability to write explanatory text.